Emodin Prevented Depression in Chronic Unpredicted Mild Stress-Exposed Rats by Targeting miR-139-5p/5-Lipoxygenase - Zhang, Teng; Yang, Can; Chu, Jiang; Ning, Lin-Na; Zeng, Peng; Wang, Xiao-Ming; Shi, Yan; Qin, Bao-Jian; Qu, Na; Zhang, Qi; Tian, Qing (Frontiers in Cell and Developmental Biology, 2021)
Background: The use of medicinal plant ingredients is one of the goals of developing potential drugs for treating depression. Compelling evidence suggests that anti-inflammatory medicines may block the occurrence of depression. We studied the effect of a natural compound, emodin, on the development of psychosocial stress-induced depression and the underlying mechanisms. Methods: Chronic unpredicted mild stress (CUMS) for seven weeks was performed to replicate psychosocial stress in rats. The sucrose preference test, force swimming test, and open field test were used to evaluate their behaviors. The differentially expressed proteins in the hippocampus were analyzed using proteomics. Nissl staining and Golgi staining were used to detect the loss of neurons and synapses, immunohistochemical staining was used to detect the activation of microglia, and the enzyme-linked immunosorbent assay was used to detect the levels of pro-inflammatory cytokines. Western blotting, immunofluorescence, and quantitative polymerase chain reaction were also performed. Results: Hippocampal inflammation with upregulated 5-lipoxygenase (5-LO) was observed in the depressed rats after CUMS exposure. The upregulation of 5-LO was caused by decreased miR-139-5p. To observe the effect of emodin, we screened out depression-susceptible (DeS) rats during CUMS and treated them with emodin (80 mg/kg/day). Two weeks later, emodin prevented the depression behaviors in DeS rats along with a series of pathological changes in their hippocampi, such as loss of neurons and spines, microglial activation, increased interleukin-1β and tumor necrosis factor-α, and the activation of 5-LO. Furthermore, we demonstrated that emodin inhibited its excess inflammatory response, possibly by targeting miR-139-5p/5-LO and modulating glycogen synthase kinase 3β and nuclear factor erythroid 2-related factor 2. Conclusion: These results provide important evidence that emodin may be a candidate agent for the treatment of depression and established a key role of miR-139-5p/5-LO in the inflammation of depression.